2014
DOI: 10.3844/crdsp.2014.17.21
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Malocclusion and Oral Habits

Abstract: In addition to heredity, oral habits are considered important factors in the etiology of malocclusion. This study was taken to assess the relationship between Malocclusion and Oral Habits. The sample comprised of 674 orthodontically untreated subjects, 324 males (48%) and 350 females (52%) 12 to 15-year-old schoolchildren from the southern part of Italy. Orthodontic variables and oral habits including mouth breathing and swallowing pattern; thumb, finger and lip sucking; and nail biting of the patients were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
3
2
0
2
Order By: Relevance
“…Oral habits such as mouth breathing,abnormal swallowing,thumb sucking,lip sucking and nail biting can have direct effect on the stomatognathic system of the body (Agarwal et al,2012) (Agarwal et al, 2014).One such abnormal factor which caused abnormal malocclusion is in patients suffering from oral submucous fibrosis were the patients has difficulty in mouth opening and caused continuous clenching of the teeth which further lead to bruxism (Harini and Leelavathi, 2019;Neralla et al, 2019)(Pratha, Ashwatha Pratha and Prabakar, 2019)(Pavithra, Preethi Pavithra and Jayashri, 2019) Many authors have written about the relationship between bad habits and malocclusion,Oral habits are repetitive behaviour in the oral cavity that results in loss of tooth structure and include biting,nail biting,bruxism,self injurious habit and tongue thrusting (Garde et al, 2014).Their effect is dependent on the nature of onset,duration of habits.Persistent habit will have effect in stomatognathic system leading to imbalance between muscles (Bell et al, 2011). In our study it was found that the highest prevalence of deleterious oral habits was biting.which was common in 32.9%.It is a similar study which has a about 65% (Giugliano et al, 2014).The habit of mouth breathing was seen in 15%.It was lower when compared to Garde et al (Garde et al, 2014). Our study found that the prevalence of class II molar relation is less when compared to the study conducted in Thailand and Pakistan (Garde et al, 2014;Sasigornwong et al, 2016)and similar to India(Sridharan et al, 2011).Other types of malocclusion associated with tongue thrusting is swallowing was also found in the study.But it was not found in other studies (Aslam, 2010)(Jalaly, Ahrari and Amini, 2009)(Al-Atabi, 2013) (Melsen, Stensgaard and Pedersen, 1979).…”
Section: Ethical Approvalsupporting
confidence: 50%
“…Oral habits such as mouth breathing,abnormal swallowing,thumb sucking,lip sucking and nail biting can have direct effect on the stomatognathic system of the body (Agarwal et al,2012) (Agarwal et al, 2014).One such abnormal factor which caused abnormal malocclusion is in patients suffering from oral submucous fibrosis were the patients has difficulty in mouth opening and caused continuous clenching of the teeth which further lead to bruxism (Harini and Leelavathi, 2019;Neralla et al, 2019)(Pratha, Ashwatha Pratha and Prabakar, 2019)(Pavithra, Preethi Pavithra and Jayashri, 2019) Many authors have written about the relationship between bad habits and malocclusion,Oral habits are repetitive behaviour in the oral cavity that results in loss of tooth structure and include biting,nail biting,bruxism,self injurious habit and tongue thrusting (Garde et al, 2014).Their effect is dependent on the nature of onset,duration of habits.Persistent habit will have effect in stomatognathic system leading to imbalance between muscles (Bell et al, 2011). In our study it was found that the highest prevalence of deleterious oral habits was biting.which was common in 32.9%.It is a similar study which has a about 65% (Giugliano et al, 2014).The habit of mouth breathing was seen in 15%.It was lower when compared to Garde et al (Garde et al, 2014). Our study found that the prevalence of class II molar relation is less when compared to the study conducted in Thailand and Pakistan (Garde et al, 2014;Sasigornwong et al, 2016)and similar to India(Sridharan et al, 2011).Other types of malocclusion associated with tongue thrusting is swallowing was also found in the study.But it was not found in other studies (Aslam, 2010)(Jalaly, Ahrari and Amini, 2009)(Al-Atabi, 2013) (Melsen, Stensgaard and Pedersen, 1979).…”
Section: Ethical Approvalsupporting
confidence: 50%
“…Keadaan ini dapat mencetuskan terjadinya maloklusi. 7 Beberapa contoh kebiasaan buruk oral di antaranya adalah mengisap ibu jari, bernapas lewat mulut, menggigit bibir ataupun kuku 8 , bruxism, dan prolonged bottle-feeding. 9 Anak-anak yang tinggal di panti asuhan cenderung memiliki perilaku mengisap ibu jari lebih tinggi daripada anak yang diasuh dalam keluarga.…”
Section: Pendahuluanunclassified
“…Kebiasaan buruk oral sebenarnya dapat terjadi untuk sementara waktu, namun apabil terus berlanjut maka dapat menyebabkan kesehatan gigi yang buruk hingga maloklusi. 7 Kebiasaan buruk oral yang tidak segera ditangani pun dapat berdampak pada gangguan sistem stomatognasi. 15…”
Section: Pembahasanunclassified
“…Therefore, the failure to do so cannot be corrected without first addressing these reflex activities. There are few studies on the association of deleterious habits with sagittal, vertical and transverse dental malocclusion [16][17][18][19][20]; and it is still under discussion whether oral habits and mouth breathing are part of the etiology of malocclusions [21], however, the recent results of this research mention that bad habits and mouth breathing are risk factors for malocclusion [22], in addition, studying the cause-effect relationship between malocclusions and deleterious habits is relevant for an adequate intervention in the treatment and to obtain better results.…”
Section: Introductionmentioning
confidence: 99%